NEGOTIATING REPRODUCTIVE AGENCY: SOCIAL REGULATION AND EMBODIED KNOWLEDGE IN BUGIS-MAKASSAR WOMEN’S RESPONSES TO PREGNANCY RISK - Cindy Israeni Ansar (JCI Publisher, 2025)
This study explores how Bugis-Makassar women construct and navigate plural reproductive knowledge in response to abortus imminens (threatened miscarriage), drawing on Talcott Parsons’ AGIL framework to analyze the sociocultural functions of care practices. Based on ethnographic fieldwork in Makassar, Indonesia, including interviews and participant observation with ten pregnant women, the study reveals that reproductive behavior is shaped by adaptive strategies (A), collective goals (G), moral integration (I), and intergenerational transmission of norms (L). Rather than following a singular medical logic, women mobilize syncretic forms of care that blend biomedical treatment, spiritual rituals, and ancestral taboos. These plural responses reflect not only epistemic hybridity but also reproductive governance enacted through kinship, religious authority, and clinical institutions. Women's agency is expressed not through open resistance, but through strategic moral navigation and embodied alignment with normative expectations—a form of what Mahmood terms the ethics of self-formation. The findings challenge biomedical-centric approaches to maternal health and highlight the need for culturally responsive interventions that respect local logics of risk, protection, and care. This study contributes to sociological debates on medical pluralism, moral regulation, and the reproduction of gendered knowledge in the Global South.